Identification, classification and expression analysis of the Ras superfamily genes in the Pacific white shrimp, Litopenaeus vannamei - Si, Shuqing; Zhang, Xiaojun; Yuan, Jianbo; Zhang, Xiaoxi; Yu, Yang; Yang, Song; Li, Fuhua (Frontiers in Marine Science, 2023)
The Ras superfamily of small guanosine triphosphatases (GTPases) are a large group of small GTP-binding proteins, which play crucial roles in basic cellular processes in all eukaryotes. In this study, by analyzing the gene structure, temporal and spatial expression patterns, a total of 108 Ras superfamily genes were identified in the genome of the Pacific white shrimp Litopenaeus vannamei. We found these genes included not only the classical Ras GTPase superfamily members, but also some unconventional and novel Ras GTPase proteins, which have unknown functions and unique expression patterns. All Ras superfamily genes of L. vannamei were highly conserved within the core G domain and closely related in phylogeny, but they might have two different evolutionary origins. In addition, different Ras GTPase genes exhibited distinct expression patterns in different tissues, development/molting stages and WSSV infection samples of L. vannamei, suggesting that they may have a high functional specialization, and play important roles in regulating the biological processes of cell differentiation, growth and development, immune response, etc. This study provides important clues for the structure, classification, evolution and function of Ras superfamily in shrimp.